2017
DOI: 10.1084/jem.20160442
|View full text |Cite
|
Sign up to set email alerts
|

Regression of apoptosis-resistant colorectal tumors by induction of necroptosis in mice

Abstract: He et al. demonstrate that SMAC mimetic is efficient to target caspase-8–deficient colorectal cancer by induction of necroptosis. This study represents an attractive strategy for overcoming apoptosis resistance in colorectal cancer for the development of more effective personalized therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 23 publications
3
51
0
Order By: Relevance
“…Recently, He et al . have demonstrated in both a genetic and a xenograft mouse model that induction of necroptosis is a plausible strategy for overcoming cell death resistance in caspase‐8 deficient colorectal cancer.…”
Section: Are Necroptotic Cancer Cells Immunogenic?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, He et al . have demonstrated in both a genetic and a xenograft mouse model that induction of necroptosis is a plausible strategy for overcoming cell death resistance in caspase‐8 deficient colorectal cancer.…”
Section: Are Necroptotic Cancer Cells Immunogenic?mentioning
confidence: 99%
“…Recently, He et al 44 Initial work showed that necroptotic fibrosarcoma L929 cells subjected to TNF-induced necroptosis do not induce pro-inflammatory cytokine production in macrophages in vitro. 45 Similarly, B16 mouse melanoma cells in which necroptosis was triggered by over-expression of FADD-death domain were unable to induce maturation of dendritic cells.…”
Section: Are Necroptotic Cancer Cells Immunogenic?mentioning
confidence: 99%
“…Earlier studies showed that, in apoptosis-resistant leukemia cells, SMs can potentiate TNF-induced necroptosis by enhancing the formation of the necrosome complex [84,115]. Subsequently, SM treatment induced massive cell death and led to regression of tumors in solid tumors [116,117]. These findings indicated that SMs can combine with death receptors to trigger apoptotic cell death.…”
Section: Combined With Death-inducing Ligandsmentioning
confidence: 93%
“…For example, mutations in Casp8 were observed in ~30% of the hypermutated colorectal cancer (CRC) samples (64). He et al directly tested the consequences of necroptosis in these cells by crossing ApcMin/+ CRCprone mice to intestinal epithelium-deleted Casp8 -/-mice (Casp8ΔIEC) (64) or by using xenografts of HT29 cells with CRISPR-deleted Casp8. In both cases, unbridled activation of RIPK1 following administration of a clinical SMAC mimetic LCL161 led to massive activation of cell death in vivo, presumably through necroptosis, and tumor regression.…”
Section: Reviewmentioning
confidence: 99%
“…Activation of RIPK1/RIPK3-dependent apoptosis or necroptosis typically requires additional modifiers, such as inhibition of cIAPs for activation of RIPK1 kinase-dependent apoptosis (73,74) and/or inhibition of caspase-8 for RIPK1/RIPK3 kinasedependent necroptosis (64,66,75,76). Consequently, Moriwaki et al examined cell death in response to a panel of commonly used chemotherapeutic agents and did not observe any changes in cell death upon knockdown of either RIPK1 or RIPK3 in RIPK3-expressing cells or upon overexpression of RIPK3 in cells that lost RIPK3 expression(37), suggesting that RIPK1/RIPK3 may not be generally involved in chemotherapy-induced cell death.…”
Section: Roles Of Ripk1/ripk3 In Immunogenic Cell Death Responses Tomentioning
confidence: 99%